Investigation of Separated Two-Phase Thermosiphon Loop for Relieving the Air-Conditioning Loading in Datacenter - Hafiz M. Daraghmeh; Mohammed W. Sulaiman; Kai-Shing Yang; Chi-Chuan Wang (Energies, 2018)
This study investigates the feasibility of using R-134a filled separated two-phase thermosiphon loop (STPTL) as a free cooling technique in datacenters. Two data center racks one of them is attached with fin and tube thermosiphon were cooled by CRAC unit (computer room air conditioning unit) individually. Thermosiphon can help to partially eliminate the compressor loading of the CRAC; thus, energy saving potential of thermosiphon loop was investigated. The condenser is a water-cooled design and perfluoroalkoxy pipes were used as adiabatic riser/downcomer for easier installation and mobile capability. Tests were conducted with filling ratio ranging from 0 to 90%. The test results indicate that the energy saving increases with the rise of filling ratio and an optimum energy savings of 38.7% can be achieved at filling ratios of 70%, a further increase of filling ratio leads to a reduction in energy saving. At a low filling ratio like 10%, the evaporator starves for refrigerant and a very uneven air temperature distribution occurring at the exit of data rack. The uneven temperature distribution is relieved considerably when the evaporator is fully flooded. It is also found that the energy saving is in line with the rise of system pressure. Overfilling of the evaporator may lead to a decline of system pressure. A lower thermal resistance occurs at high filling ratios and higher ambient temperature.